Evaluation of water beef buffalo from birth to two years using different growth curves - Ramos, Alcides Amorim [UNESP]; DeSouza, J. C.; Malhado, C. H. M.; Jorge, Andre Mendes [UNESP]; Ferraz Filho, P. B.; DeFreitas, J. A.; Bacon, R. R.; Lamberson, W. R. (Pagepress Publ, 2007)
The buffalo is a domestic animal species of growing world-wide importance. Research to improve genetic improvement programs is important to maintain the productivity of buffalo. The objective this research was to evaluate the growth of Brazilian buffalo to two years of age with different growth curves. Growth curves consolidate the information contained in the weight-age data into three or four biologically meaningful parameters. The data included 31,452 weights at birth and 120, 205, 365, 550 and 730 days of buffalo (n = 5,178) raised on pasture without supplementation. Logistic, Gompertz, quadratic logarithmic, and linear hyperbolic curves (designated L, G, QL, and LH, respectively) were fitted to the data by using proc NUN of SAS (SAS Institute, Inc., Cary, NC, USA). The parameters estimates for L [WT= A * (((1 + exp (-k * AGE)))**-m)] were A = 865.1 +/- 5.42; k= 0.0028 +/- 0.00002; M= 3.808 +/- 0.007; R(2) = 0.95. For G [WT= A * exp (-b * exp (-k * age)] the parameters estimates were A= 967.6 +/- 7.23; k = 0.00217 +/- 0.000015; b = -2.8152 +/- 0.00532. For QL [WT= A + b*age + k*(age*age) + m*log (age)] parameters estimates were A= 37.41 +/- 0.48; k= 0.00019 +/- 6.4E(-6); b= 0.539 +/- 0.006; m= 2.32 +/- 0.23; R(2)=0.96. For LH [WT= A + b*AGE + k*(1/AGE)] the parameters estimates were A= 23.15 +/- 0.44; k=15.16 +/- 0.66; b= 0.707 +/- 0.001; R(2)= 0.96. Each of these curves fit these data equally well and could be used for characterizing growth to two years in beef buffalo.
Keywords: Buffalo; Growth Curve; Weight